Somatic profiling of the epidermal growth factor receptor pathway in tumors from patients with advanced colorectal cancer treated with chemotherapy ± cetuximab. - Smith, C; Fisher, D; Claes, B; Maughan, T; Idziaszczyk, S; Peuteman, G; Harris, R; James, MD; Meade, A; Jasani, B; Adams, R; Kenny, S; et al. (2013)
PURPOSE: To study the somatic molecular profile of the EGF receptor (EGFR) pathway in advanced colorectal cancer, its relationship to prognosis, the site of the primary and metastases, and response to cetuximab. EXPERIMENTAL DESIGN: We used Sequenom and Pyrosequencing for high-throughput somatic profiling of the EGFR pathway in 1,976 tumors from patients with advanced colorectal cancer from the COIN trial (oxaliplatin and fluoropyrimidine chemotherapy ± cetuximab). Correlations between mutations, clinicopathologic, response, and survival data were carried out. RESULTS: Sequenom and Pyrosequencing had 99.0% (9,961/10,063) genotype concordance. We identified 13 different KRAS mutations in 42.3% of advanced colorectal cancers, 2 BRAF mutations in 9.0%, 4 NRAS mutations in 3.6%, and 5 PIK3CA mutations in 12.7%. 4.2% of advanced colorectal cancers had microsatellite instability (MSI). KRAS and PIK3CA exon 9, but not exon 20, mutations cooccurred (P = 8.9 × 10(-4)) as did MSI and BRAF mutations (P = 5.3 × 10(-10)). KRAS mutations were associated with right colon cancers (P = 5.2 × 10(-5)) and BRAF mutations with right (P = 7.2 × 10(-5)) and transverse colon (P = 9.8 × 10(-6)) cancers. KRAS mutations were associated with lung-only metastases (P = 2.3 × 10(-4)), BRAF mutations with peritoneal (P = 9.2 × 10(-4)) and nodal-only (P = 3.7 × 10(-5)) metastases, and MSI (BRAF(WT)) with nodal-only metastases (P = 2.9 × 10(-4)). MSI (BRAF(WT)) was associated with worse survival (HR = 1.89, 95% CI 1.30-2.76, P = 8.5 × 10(-4)). No mutations, subsets of mutations, or MSI status were associated with response to cetuximab. CONCLUSIONS: Our data support a functional cooperation between KRAS and PIK3CA in colorectal tumorigenesis and link somatic profiles to the sites of metastases. MSI was associated with poor prognosis in advanced disease, and no individual somatic profile was associated with response to cetuximab in COIN.